Analysis of Socioeconomic and Situational Factors, Winning Probability, and Perception of Convenience on Online Gambling Addiction Among Gen Z - Sovy Muti Ardianty Hasibuan; Andri Soemitra; Muhammad Syukri Albani (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Online gambling refers to the act of betting or wagering on games of chance or skill via the internet. It typically involves various forms of gambling, such as online casinos, sports betting, poker, and lotteries, where individuals can place bets using real money through digital platforms or mobile applications. The purpose of this study is to analyze socio-economic factors, situational, probability of winning and perception of ease of addiction to playing online gambling in gen z in the city of Medan.  This study uses a quantitative method with data collection from questionnaires. The sample is 100 responden focused on Gen Z with an early adult age of 18 to 25 years who were involved in online gambling games. The data collected for this study was processed and analyzed using regression in SPSS. Socioeconomic factors had a positive and significant effect on online addiction, situational factors also had a positive and significant effect on online gambling addiction, winning probability factors had a positive and significant effect on online gambling addiction and convenience perception factors had a negative and non-significant effect. The novelty of this research lies in its multidimensional approach to analyzing online gambling addiction among Generation Z in Medan City and give integrated approach offers new insights into the dynamics of online gambling addiction, especially in a local context.